Counselling and Training of Nutritional Snacks Making for Immunity Increasing During Covid 19 Pandemic - Siahaan, Ginta; Manalu, Mincu; Rumida; Ginting, Riska S; Manurung, Aprianti; Sihombing, Loika; Farida, Farida; Akmal, Ahmad RI (Talenta Publisher Universitas Sumatera Utara, 2022)
Increasing body immunity is very necessary after the Covid-19 pandemic. One of the efforts that can be made to increase the body's immunity is to consume functional foods with immunostimulant activity, such as processed snakehead fish products in the form of nuggets, and